AnaIisis Kepuasan Pengguna Pada PeIayanan FasiIitas di TerminaI Condongcatur Kabupaten SIeman - Mufid, Muhammad Fadhil; Rahmita, Destria; Basuki, Ahmad (Jurnal Civil Engineering Study, 2025)
Population growth in Yogyakarta reached 0.58%, with Sleman Regency as the area with the highest concentration of 1,996.88 people/km², accounting for 30.69% of the total population of Yogyakarta. However, public interest in public transportation has declined, and operational implementation and terminal management have not been carried out optimally. This has impacted operational efficiency and user satisfaction. The objective of this study is to analyze the existing conditions and user satisfaction at Condongcatur Terminal and provide recommendations for improvements. The methods used include observation to analyze existing conditions based on PM No. 40 of 2015 regarding Standards for Passenger Terminal and Road Transport Services, and measuring user satisfaction through the distribution of questionnaires via links and QR codes. The analysis was conducted using the Customer Satisfaction Index (CSI) method to measure satisfaction levels and the Importance Performance AnaIysis (IPA) method to provide facility recommendations in Quadrant I. The analysis of the existing conditions revealed that only 20 out of 33 indicators (61%) of facilities were available. The user satisfaction level based on the CSI was 49.77%, categorized as “less satisfied,” and the IPA results showed that 64% were in the “not meeting expectations” category. The types of services in Quadrant I, namely pedestrian lanes, evacuation routes, fire extinguishers, security personnel, waiting areas, toilets, cleaning facilities and staff, and service information, need to be prioritized for improvement. This is because these services are considered important by users, but their implementation is not yet satisfactory.